2015
DOI: 10.1039/c5cp02393a
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the enhanced Li+ ionic conductivity in Gd+3 substituted Li5+2xLa3Nb2−xGdxO12 lithium conducting garnets

Abstract: In the present study, we report the synthesis and the Li(+)-ion conductivity of new Gd(+3) substituted Li5+2xLa3Nb2-xGdxO12 (x = 0.0, 0.25, 0.4, 0.5, 0.6) garnets. The structural study by XRD showed that pure cubic garnet phases were obtained with upto x = 0.5 composition. With the further increase of the Gd(+3) content to x≥ 0.6, secondary phases are observed. The ionic conductivity was studied by impedance spectroscopy. We found that the Li(+) ionic conductivity increased with increasing Gd(+3) content with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The peaks match well with cubic garnet Li 5 La 3 Nb 2 O 12 (PDF 80-0457). Li 5 La 3 M 2 O 5 (M = Nb, Ta) is the first structural example of a rapid, Li-ion conductive garnet and is the conventional structure used to study the garnet-type LLZO materials (26,(46)(47)(48). Electrochemical impedance spectroscopy (EIS) was used to measure the Li-ion conductivity of sintered LLCZN.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks match well with cubic garnet Li 5 La 3 Nb 2 O 12 (PDF 80-0457). Li 5 La 3 M 2 O 5 (M = Nb, Ta) is the first structural example of a rapid, Li-ion conductive garnet and is the conventional structure used to study the garnet-type LLZO materials (26,(46)(47)(48). Electrochemical impedance spectroscopy (EIS) was used to measure the Li-ion conductivity of sintered LLCZN.…”
Section: Resultsmentioning
confidence: 99%
“…97 The disagreement between the experimental and predicted values was acceptable (B0.2 in log s tot ) for Li 102 were systematically underestimated by models that included the difference in the experimental temperatures, the oxygen nonstoichiometry of these compounds or their instability to moisture. 103 In contrast, the total conductivities of Gd 3+ -substituted LLN 79 were overestimated by the models, except those for LLN-Gd60 (impurity phases were observed for this particular compound). The incorrect predictions for these compounds as well as for supervalent (Ce 4+ )-substituted LLZO Li 6.6 La 2.6 Ce 0.4 Zr 2 O 12 104 remain unexplained.…”
Section: Predictive Ability Of Modelsmentioning
confidence: 74%
“…It is suggested that Sm 3+ substitutions in LLN garnets will force Li + ions at 24d sites to leave their positions and move to occupy 48 g/96 h octahedral sites [33][34][35]. This process will allow more vacant 24d sites, which are essential for 3D diffusion process through the 24d-96h-48g-96h-24d chain pathway, as illustrated in Figure 6 [27,[33][34][35][36]. The relaxation dynamics of the LLN-Sm ceramics are studied by the complex electric modulus M * (ω), which can be expressed as follows [37]:…”
Section: Resultsmentioning
confidence: 99%
“…Although most research work on lithium garnet materials is directed towards Li 7 La 3 Zr 2 O 12 , high ionic conductivity values in the 10 −4 S/cm range could also be obtained in doped Li 5 La 3 Nb 2 O 12 (LLN) and Li 5 La 3 Ta 2 O 12 (LLT) materials [21,[27][28][29][30]. In our recent work on Gd 3+ −substituted Li 5+2x La 3 Nb 2−x Gd x O 12 , the ionic conductivity was found to increase to 1.12 × 10 −4 S/cm for x = 0.5, which is about two orders of magnitude higher than the un-doped LLN material [27]. Similarly, Sc 3+ doping in Li 5+2x La 3 Nb 2−x Sc x O 12 garnets leads to ionic conductivity of 3.7 × 10 −4 S/cm for x = 0.625 [28].…”
Section: Introductionmentioning
confidence: 99%